Peter Frederic Strawson’s metaphysics - Besler, Gabriela (Folia Philosophica, 2000)
The present article shows the metaphysic of a philosopher whose influence greatly helped to overcome the non-metaphysical, and anti metaphysical attitude of the analytic philosophy. Strawson claims that the task of philosophy cannot be reduced to removing linguistic misunderstandings, but rather includes task of dealing, in a positive sense, with traditional metaphysical problems. Strawson’s contribution to metaphysics consists in his having determined the conditions and criteria of being an individual entity, his combining of existence with individual being, and in his showing the links between indivudual and general beings. It should be added that, within the limits of his understanding of metaphysics, he accepts the claims of metaphysical and epistemological realsim.